Modeling the Spread of Dengue Fever Post-Flood in Jakarta: Evaluation of the Effectiveness of Mosquito Vector Control Strategies - Hairudin La Patilaiya; Made Dewi Sariyani; Junardin Djamaluddin; Risnawati Tanjung; Jernita Sinaga (CV. Get Press Indonesia, 2025)
Dengue Hemorrhagic Fever (DHF) remains one of the most significant public health challenges in tropical and subtropical regions, including Indonesia. This study uses a quantitative approach with an analytical observational design, combined with mathematical modeling and spatial analysis to understand the spread of dengue fever after the Jakarta floods in Jakarta. Specifically, this study utilizes a Geographic Information System (GIS) to map the distribution of DHF cases before and after the floods, and applies differential-based epidemiological models such as SEIR or modified SIR to describe transmission dynamics influenced by post-flood environmental conditions, particularly waterlogging, rainfall, humidity, and demographic factors such as population density. Descriptive and correlational findings indicate that high rainfall, increased humidity, extensive inundation index, and extensive humidity are consistently associated with increased DHF incidence. Moreover, the results of this study provide a scientific basis for public health policy planning and disaster mitigation, particularly in dense, flood-prone urban settings like Jakarta.